Preoperative Upper Gastrointestinal Endoscopy Prior to Sleeve Gastrectomy: To Do, or Not to Do - Okay, Nermin D.; Yıldız, Barış D. (Journal of Health and Allied Sciences NU, 2022)
There is controversy about the requirement of preoperative upper gastrointestinal (GI) endoscopy for sleeve gastrectomy patients. The aim of this study is to understand the necessity of a preoperative upper GI endoscopy before sleeve gastrectomy. In this study, the incidental findings encountered in sleeve gastrectomy pathology specimens of a cohort of patients were analyzed. A total of 270 patients who had sleeve gastrectomy at Ankara Numune Teaching Hospital, General Surgery Clinic, between 2011 and 2016 were evaluated. Histopathological examination of sleeve gastrectomy specimens was performed. Chronic gastritis in 76.6% and intestinal metaplasia in 4.1% of patients were observed. A GI stromal tumor was found in one male patient. Also, an active gastric ulcer was detected in one patient. Only 13 (4.9%) out of 270 patients had a postoperative pathology needing follow-up. None of our findings would have an impact of changing the surgical approach. Therefore, the results of this study suggested that application of a preoperative GI endoscopy is not necessary prior to sleeve gastrectomy in patients without upper GI symptoms.
Keywords: endoscopy; gastrointestinal stromal tumor; obesity; sleeve gastrectomy